2020
DOI: 10.1002/jts.22483
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of a Web‐Based Intervention to Disseminate Clinical Practice Guidelines for Posttraumatic Stress Disorder: The PTSD Clinicians Exchange

Abstract: Delivery of best-practice care for posttraumatic stress disorder (PTSD) is a priority for clinicians working with active duty military personnel and veterans. The PTSD Clinicians Exchange, an Internet-based intervention, was designed to assist in disseminating clinically relevant information and resources that support delivery of key practices endorsed in the Veterans Administration (VA)-Department of Defense (DoD) Clinical Practice Guidelines (CPG) for the Management of Posttraumatic Stress. We conducted a ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…One study that evaluated the effect of a web-based intervention to disseminate CPG for post-traumatic stress disorder (PTSD) among clinicians, including VA and DoD providers, found that web-based resources may support comprehensive efforts to disseminate CPG. 11 Another study that tested an online military-focused PTSD training for primary care practitioners in VA hospitals found that the training improved providers' PTSD knowledge. 12 There remains, however, a gap in understanding the degree to which these types of interventions can aid military medical providers' uptake of clinical practice guidelines as it relates to OT for chronic pain.…”
mentioning
confidence: 99%
“…One study that evaluated the effect of a web-based intervention to disseminate CPG for post-traumatic stress disorder (PTSD) among clinicians, including VA and DoD providers, found that web-based resources may support comprehensive efforts to disseminate CPG. 11 Another study that tested an online military-focused PTSD training for primary care practitioners in VA hospitals found that the training improved providers' PTSD knowledge. 12 There remains, however, a gap in understanding the degree to which these types of interventions can aid military medical providers' uptake of clinical practice guidelines as it relates to OT for chronic pain.…”
mentioning
confidence: 99%